Empathy as a Predictor of Behavioral Problems in Early Childhood: A Gender-Based Analysis - Ainur Rosyidah Kusuma; Liftiah; Diana (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Unaddressed behavioral problems in early childhood often persist into later life stages. This study aimed to analyze how empathy levels influence behavioral problems among young children and whether this relationship remains significant after controlling for gender. Using an explanatory quantitative design, data were obtained from 141 kindergarten and RA B teachers in Semarang City through a structured questionnaire. The results of frequency analysis showed that children’s empathy levels were entirely within the high category (100%), while behavioral problems were mostly in the low category (70.9%) and moderate category (29%). Multiple regression testing confirmed that empathy significantly reduced problem behaviors (p < 0.05). Emotional contagion, concern for others, and prosocial behavior were the most influential dimensions. When gender was controlled, empathy remained a significant predictor, whereas gender had no direct effect. This study contributes to the growing body of global scholarship on early childhood socio-emotional development by highlighting empathy as a key psychological mechanism for behavioral regulation. It strengthens the theoretical integration between empathy development and behavioral adjustment, offering empirical evidence that supports cross-cultural understanding of emotional and behavioral competencies in early childhood education. The findings suggest that interventions emphasizing emotional contagion, caring, and prosocial responsiveness can effectively reduce behavioral issues regardless of gender. Further studies are recommended to explore cross-contextual factors such as emotional regulation, family interactions, and teacher–child relationships to enrich the explanatory model of empathy’s influence on children’s behavioral outcomes.